Air Pressure-Assisted Centrifugal Dewatering of Concentrated Fine Sulfide Particles. (8th June 2011) - Asmatulu, R.
Abstract : An air pressure-assisted centrifugal dewatering method was developed and used for the dewatering of concentrated finesulfide particles, such as sphalerite, galena, and chalcopyrite. This filtration method was mainly designed to increase the filtration rate during the drainage cycle and, hence, produce drier filter cakes, which in turn could reduce the cost and emission problems/concerns of thermal dryers in the preparation plants. Several dewatering parameters, including applied pressure, centrifugal force ( G -force), spin time, cake thickness, and surface hydrophobization, were tested to optimize the processing conditions. Test results showed that, at higher air pressure and centrifugal force, the cake moisture reduction was more than 70%, depending on the testing conditions. As a result, it can be-concluded that the novel filtration method effectively works on the dewatering of fine particles (–150  μ m).